A mussel-mimic adhesive silicone marine antifouling coating
Patent Information
- Application Number
- CN202411683061.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-11-22
AI Technical Summary
然而,许多传统防污涂料中的有毒成分对海洋生物和生态环境有较大破坏性,会在海洋中逐渐累积,产生生态毒性
[0045]1.尽管甲基乙烯基MQ型硅树脂具有不饱和基团,但是由于该基团直接连接在硅氧网络测量上,因此其空间位阻较大,在自由基聚合反应时难以接近并有效聚合。而引入不饱和五氟苯酚酯单体的一类具有高反应活性的氮气,能够形成稳定的自由基中间体。当甲基乙烯基MQ型硅树脂、不饱和五氟苯酚酯单体、不饱和丙烯酸酯单体共同进行自由基聚合反应时,可以产生自由基共聚反应的“交替”效应,即不饱和五氟苯酚酯单体和不饱和丙烯酸酯单体产生的稳定自由基可以有效引导至甲基乙烯基MQ型硅树脂的不饱和结构中,可以形成稳定的共聚产物,克服单独甲基乙烯基MQ型硅树脂难以进行自由基聚合反应的缺点。
Smart Images

Figure BDA0005148839840000031 
Figure BDA0005148839840000032 
Figure BDA0005148839840000061
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of marine antifouling coating technology and underwater coating protection technology, and specifically relates to a functionalized modified fouling-releasing marine antifouling coating. Background Technology
[0002] Traditional marine antifouling coatings primarily rely on heavy metal oxides, such as copper oxide, or organotin compounds (such as tributyltin, TBT) as active ingredients. These coatings inhibit or kill attached organisms by releasing heavy metal ions or toxic substances. However, many toxic components in traditional antifouling coatings are highly destructive to marine life and the ecosystem, accumulating gradually in the ocean and causing ecotoxicity. Compounds such as tributyltin have long been proven to cause serious ecological damage to the marine environment, and therefore, many countries have legislated to prohibit or restrict their use. Therefore, the search for non-toxic and environmentally friendly antifouling coatings is urgently needed.
[0003] Driven by environmental protection requirements, fouling-release marine antifouling coatings based on polysiloxanes have gradually become a research hotspot in recent years. Polysiloxanes are polymeric materials based on silicon-oxygen bonds, possessing excellent corrosion resistance, low surface energy, and good thermal stability. They are also not easily degraded and exhibit good stability in marine environments. Polysiloxane-based antifouling coatings primarily utilize their low surface energy to prevent biofouling. Their smooth surface structure reduces adhesion strength, making it easier for biofouling to detach under water flow impact, thus achieving a fouling release effect. These coatings are non-toxic and environmentally friendly, avoiding the impact of toxic components in traditional antifouling coatings on the marine environment. They are an environmentally friendly marine antifouling material that meets the needs of sustainable development.
[0004] The main advantage of polysiloxane fouling-release antifouling coatings lies in their physical antifouling effect, which does not rely on the release of chemical toxins. This not only reduces the risk of environmental pollution but also significantly extends the service life of the material. Polysiloxanes have low surface energy, making it difficult for underwater organisms to firmly adhere to their surfaces, and they are easily detached under high-speed water flow. Unlike traditional toxic antifouling coatings, polysiloxane antifouling coatings work on the principle of physical barrier and self-cleaning, that is, removing fouling by reducing the adhesion of fouling materials and using fluid shear forces. Although polysiloxane fouling-release antifouling coatings have significant environmental protection and antifouling effects, they also face some challenges in application. First, polysiloxane molecules generally exhibit low mechanical strength, making them susceptible to damage, especially in harsh marine environments, affecting their antifouling performance. Second, polysiloxane materials have poor adhesion, especially in high-velocity water environments, where the coating may peel off or crack, leading to a decrease in antifouling effectiveness and the need for frequent maintenance and repair.
[0005] Poor adhesion is a significant problem for polysiloxane-based fouling-release antifouling coatings. While the low surface energy resulting from the silicon-oxygen bonds between polysiloxane molecules helps reduce biofouling, it also weakens the bond between the coating and the substrate. This deficiency is particularly pronounced in marine applications, where complex physical and chemical conditions such as salt spray, ultraviolet radiation, tidal changes, and seawater erosion place high demands on coating adhesion. Furthermore, the poor flexibility of polysiloxanes makes them prone to cracking on the substrate surface, further reducing adhesion. Therefore, significantly improving the adhesion of polysiloxane antifouling coatings while maintaining excellent antifouling performance remains a major challenge in current research and application.
[0006] To address this issue, some current research attempts to enhance the adhesion between polysiloxane protons and substrates through chemical bonding. For example, this can be achieved by introducing functional groups that can form chemical bonds with the substrate into the polysiloxane molecule, or by using surfactants to improve the interfacial affinity between the coating and the substrate. Furthermore, copolymerizing or compounding polysiloxanes with other polymers such as polyurethane and epoxy resins is another approach, aiming to optimize the elastic modulus of the coating to adapt to complex marine environments. However, these modification measures often affect the low surface energy characteristics of polysiloxanes, thus requiring a trade-off between various performance characteristics in practical applications. Summary of the Invention
[0007] Traditional fouling-releasing polysiloxane-based marine antifouling coatings suffer from poor adhesion to the substrate or intermediate coat due to the material properties inherent in their polymer molecular structure. This leads to problems such as easy detachment and low stability during actual service. Therefore, it is necessary to improve their adhesion performance without compromising their antifouling effect (utilizing low surface energy for antifouling). This invention aims to provide a mussel-like adhesive silicone marine antifouling coating. By leveraging the molecular structure of dopamine, the main secretion of mussel adhesive fibers, catechol structural groups are grafted into a nonpolar siloxane structure, thereby achieving strong adhesion to the substrate or intermediate coat using the catechol structure. The difference in molecular polarity and flexibility between the dopamine-modified polysiloxane polymer and the hydrophobic polysiloxane polymer allows for polymer phase separation. The hydrophobic siloxy group structure (derived from the hydrophobic polysiloxane polymer molecule) is exposed on the coating surface, ensuring excellent low surface energy properties. The adhesive catechol structure (derived from dopamine-modified polysiloxane polymer) is enriched at the interface between the coating and the substrate or intermediate coat. The final cured coating maintains excellent adhesion to the interface between the coating and the substrate or intermediate coat, while the coating surface maintains excellent low surface energy properties, thus providing excellent antifouling performance.
[0008] This invention is implemented through the following technical solutions:
[0009] In a first aspect, the present invention provides an organosilicon marine antifouling coating for preventing mussel adhesion, comprising, by weight fraction: (1) 15 to 30 parts of component A; (2) 4 to 8 parts of component B; and (3) 0.5 to 1 part of component C;
[0010] in,
[0011] Component A comprises, by weight:
[0012]
[0013] Component B comprises, by weight:
[0014]
[0015] The dopamine-modified polysiloxane polymer was prepared by a combination of free radical copolymerization and ammonolysis, with the specific steps as follows:
[0016] (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ type silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent are added in sequence, and then the temperature is raised to 65-75℃ and reacted for 5-8 hours.
[0017] (2) Pour the reaction product into methanol at 5°C and filter it multiple times. Dry the filtered product under vacuum conditions to obtain the prepolymer.
[0018] (3) In an argon-protected reactor, add the prepolymer, followed by the dried dimethylformamide, dopamine salt monomer, and triethylamine, and then stir the reaction at room temperature for 20-26 hours.
[0019] (4) The product after the reaction was precipitated into an excess of 0.5wt% hydrogen chloride aqueous solution, and the polymer was recovered by filtration. Then, a large amount of deionized water was used for precipitation purification. Finally, the purified polymer was dried and collected under vacuum conditions.
[0020] Preferably, the unsaturated pentafluorophenol ester monomer is selected from one of pentafluorophenyl acrylate, pentafluorophenyl methacrylate, and 4-vinylphenyl pentafluorobenzoate.
[0021] Preferably, the unsaturated MQ type silicone resin is selected from methyl vinyl MQ type siloxane resin, with an M:Q value ≥ 1.3:1, or the methyl vinyl MQ type silicone resin is liquid at 25°C.
[0022] Preferably, the unsaturated acrylate monomer is selected from butyl methacrylate, laurate methacrylate, and butyl acrylate.
[0023] Preferably, the chain transfer agent is a RAFT reagent, specifically selected from one of 2-(dodecylthiocarbonylthio)-2-methylpropionic acid, 2-cyano-2-propyldodecyl trithiocarbonate, cyanomethyldodecyl trithiocarbonate, and 2-(dodecylthiocarbonylthio)propionic acid.
[0024] Preferably, the solvent is selected from toluene, nitrile butyrate, and acetone.
[0025] Preferably, the weight ratio of the unsaturated pentafluorophenol ester monomer, unsaturated MQ type silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent is 2:(30-45):(5-10):(0.1-0.4):(0.5-1):(40-80).
[0026] Preferably, the dopamine salt monomer is selected from one of 6-hydroxydopamine hydrochloride, dopamine hydrochloride, and 5-hydroxydopamine hydrochloride.
[0027] Preferably, the weight ratio of the prepolymer, dimethylformamide, dopamine salt monomer, and triethylamine is (30-50):(50-120):(3-5):(5-10).
[0028] Preferably, the hydroxyl-terminated polysiloxane resin is selected from α,ω-dihydroxypolydimethylsiloxane with a viscosity of 2800-10000 mPa·s at 25°C.
[0029] Preferably, the additive is selected from at least one of wetting and dispersing agents, defoamers, and leveling agents.
[0030] Specifically, the wetting and dispersing agent is selected from BYK116 and BYK169 from BYK Corporation, and 901 and 903 from Deqian Company.
[0031] Specifically, the defoamer is selected from BYK065 and BYK066N from BYK Corporation, and EFKA2020 from Efka, Netherlands.
[0032] Specifically, the leveling agent is selected from one of BYK308, BYK310, and BYK373 from Germany.
[0033] Preferably, the pigments and fillers are common in this field and have no special requirements. As a preferred option, they are selected from, but not limited to, calcium carbonate, ferric oxide, titanium dioxide, barium sulfate, kaolin, and zinc oxide.
[0034] Preferably, the first solvent is selected from methanol, xylene, and acetone.
[0035] Preferably, the curing agent is selected from one of tetraethyl orthosilicate, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(isobutenyloxy)propyltrimethoxysilane, and γ-methacryloyloxypropyltriisopropoxysilane.
[0036] Preferably, the second solvent is selected from acetone, butanone, and acetylacetone.
[0037] Preferably, the catalyst is selected from one of dibutyltin disilicate, stannous octoate, and organobismuth.
[0038] Preferably, the third solvent is selected from acetylacetone, cyclohexanone, and toluene.
[0039] Secondly, the present invention provides a method for preparing the mussel-like adhesive organosilicon marine antifouling coating described in the first aspect. The preparation can be carried out using conventional methods. First, components A, B, and C are prepared separately and stored in a sealed container. Specifically, the method includes the following steps:
[0040] (1) Hydroxyl-terminated polysiloxane resin, dopamine-modified polysiloxane polymer, additives, and 50% of the first solvent were added sequentially to a dispersion and stirring device. The mixture was then dispersed at 100 rpm for 20 min. After that, pigments and fillers and 50% of the first solvent were added to the dispersion and stirring device, and the mixture was dispersed at the same speed for 20 min to prepare component A. The mixture was then sealed and stored.
[0041] (2) Use a dispersion and stirring device to disperse the curing agent and the second solvent at 50 rpm for 10 min to prepare component B, and then seal and store it.
[0042] (3) Use a dispersion and stirring device to disperse the catalyst and the third solvent at 50 rpm for 10 min to prepare component C, and then seal and store it.
[0043] Thirdly, the present invention also provides a coating prepared by the mussel-like adhesive organosilicon marine antifouling coating described in the first aspect, wherein components A, B, and C are mixed evenly using conventional dispersion processes and equipment, and applied by spraying, rolling, brushing, or other methods, and cured for at least 48 hours to prepare a coating with a film thickness of 150–250 μm.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] 1. Although methyl vinyl MQ type silicone resin has unsaturated groups, these groups are directly attached to the silicon-oxygen network, resulting in significant steric hindrance and making it difficult to approach and effectively polymerize during free radical polymerization. Introducing nitrogen, a highly reactive gas from unsaturated pentafluorophenol ester monomers, can form stable free radical intermediates. When methyl vinyl MQ type silicone resin, unsaturated pentafluorophenol ester monomers, and unsaturated acrylate monomers undergo free radical polymerization together, an "alternating" effect in free radical copolymerization can occur. That is, the stable free radicals generated by the unsaturated pentafluorophenol ester monomers and unsaturated acrylate monomers can be effectively guided into the unsaturated structure of the methyl vinyl MQ type silicone resin, forming a stable copolymer product. This overcomes the disadvantage of methyl vinyl MQ type silicone resin alone being difficult to undergo free radical polymerization.
[0046] 2. The pentafluorophenol groups in unsaturated pentafluorophenol ester monomers possess high reactivity and may undergo side reactions with other free radicals or reaction intermediates during conventional free radical polymerization, such as crosslinking or asymmetric chain growth, leading to loss of monomer functionality. However, the mild conditions and low free radical concentration of RAFT polymerization help avoid these side reactions, thus preserving the reactivity and functionality of the pentafluorophenol groups in pentafluorophenol acrylate. The resulting polymer can then be further functionalized in subsequent steps, retaining its specific chemical properties.
[0047] 3. Since the dopamine structure (or catechol structure), a major component of mussel secretions, is a common free radical inhibitor of aggregation, free radical copolymerization cannot introduce the catechol structure into the modified siloxane polymer. However, dopamine salt monomers can undergo ammonolysis with the pentafluorophenol structure formed in the prepolymer. In the presence of excess amine solution, the pentafluorophenol structure on the prepolymer molecular chain is replaced by the catechol structure, thereby introducing the catechol structure into the polymer molecular chain to synthesize a dopamine-modified polysiloxane polymer.
[0048] 4. The final prepared mussel-like adhesive silicone marine antifouling coating is made by uniformly mixing hydrophobic hydroxyl-terminated polysiloxane resin and dopamine-modified polysiloxane polymer through mechanical stirring. During the curing process, phase separation occurs due to the difference in molecular polarity / nonpolarity. At the same time, the hydrophobic hydroxyl-terminated polysiloxane resin undergoes a three-dimensional cross-linking reaction to form a network structure. As a result, the dopamine-modified polysiloxane polymer can be enriched in the contact area between the coating and the substrate or intermediate paint based on phase separation, giving full play to the high adhesion of catechol and achieving the effect of low surface energy antifouling and excellent adhesion. Detailed Implementation
[0049] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0050] The coating of this invention is prepared by synthesizing a dopamine-modified polysiloxane polymer and blending it with a hydrophobic hydroxyl-terminated polysiloxane resin. During the final curing process, the hydrophobic hydroxyl-terminated polysiloxane resin undergoes a cross-linking reaction to generate a three-dimensional network structure, which forms the main body of the cured coating. Meanwhile, the polar dopamine-modified polysiloxane polymer can be enriched in the bonding area between the coating and the substrate or intermediate paint through phase separation, thereby ensuring that the coating has excellent adhesion. At the same time, the coating surface still maintains the anti-fouling advantages such as low surface energy, ensuring reliable anti-fouling performance.
[0051] The raw materials used in the examples are shown in Table 1. In actual implementation, the raw materials are not limited to those listed in Table 1; appropriate products can be selected based on the foregoing. Other raw materials used in the examples are commercially available chemical reagents.
[0052] Table 1
[0053]
[0054]
[0055] Preparation of dopamine-modified polysiloxane polymer 1
[0056] The weight ratio of unsaturated pentafluorophenol ester monomer 2-1, unsaturated MQ type silicone resin 3-1, unsaturated acrylate monomer 4-1, chain transfer agent 5-2, initiator azobisisobutyronitrile, and solvent 6-1 is 2:35:5:0.3:1:70.
[0057] The weight ratio of the prepolymer, dimethylformamide, dopamine salt monomer 7-1, and triethylamine is 35:80:5:8.
[0058] The specific preparation process is as follows:
[0059] (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ type silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent were added in sequence, and then the temperature was raised to 70°C for 7 hours.
[0060] (2) Pour the reaction product into methanol at 5°C and filter it multiple times. Dry the filtered product under vacuum conditions to obtain the prepolymer.
[0061] (3) In an argon-protected reactor, the prepolymer was added, followed by the addition of dried dimethylformamide, dopamine salt monomer, and triethylamine. The mixture was then stirred and reacted at room temperature for 22 hours.
[0062] (4) The product after the reaction was precipitated into an excess of 0.5% (mass fraction) hydrogen chloride aqueous solution, and the polymer was recovered by filtration. Then, a large amount of deionized water was used for precipitation purification. Finally, the purified polymer was dried and collected under vacuum conditions.
[0063] Preparation of dopamine-modified polysiloxane polymer 2
[0064] The weight ratio of unsaturated pentafluorophenol ester monomer 2-2, unsaturated MQ type silicone resin 3-2, unsaturated acrylate monomer 4-1, chain transfer agent 5-1, initiator azobisisobutyronitrile, and solvent 6-1 is 2:30:7:0.1:0.5:40.
[0065] The weight ratio of prepolymer, dimethylformamide, dopamine salt monomer 7-2, and triethylamine is 30:120:4:10.
[0066] The specific preparation process is as follows:
[0067] (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ type silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent were added in sequence, and then the temperature was raised to 65℃ for 5h.
[0068] (2) Pour the reaction product into methanol at 5°C and filter it multiple times. Dry the filtered product under vacuum conditions to obtain the prepolymer.
[0069] (3) In an argon-protected reactor, the prepolymer was added, followed by the addition of dried dimethylformamide, dopamine salt monomer, and triethylamine. The mixture was then stirred and reacted at room temperature for 26 hours.
[0070] (4) The product after the reaction was precipitated into an excess of 0.5% (mass fraction) hydrogen chloride aqueous solution, and the polymer was recovered by filtration. Then, a large amount of deionized water was used for precipitation purification. Finally, the purified polymer was dried and collected under vacuum conditions.
[0071] Preparation of dopamine-modified polysiloxane polymer 3
[0072] The weight ratio of unsaturated pentafluorophenol ester monomer 2-3, unsaturated MQ type silicone resin 3-2, unsaturated acrylate monomer 4-2, chain transfer agent 5-3, initiator azobisisobutyronitrile, and solvent 6-2 is 2:45:10:0.4:0.6:80.
[0073] The weight ratio of prepolymer, dimethylformamide, dopamine salt monomer 7-2, and triethylamine is 50:50:3:5.
[0074] The specific preparation process is as follows:
[0075] (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ type silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent were added in sequence, and then the temperature was raised to 75°C for 8 hours.
[0076] (2) Pour the reaction product into methanol at 5°C and filter it multiple times. Dry the filtered product under vacuum conditions to obtain the prepolymer.
[0077] (3) In an argon-protected reactor, the prepolymer was added, followed by the addition of dried dimethylformamide, dopamine salt monomer, and triethylamine. The mixture was then stirred and reacted at room temperature for 20 hours.
[0078] (4) The product after the reaction was precipitated into an excess of 0.5% (mass fraction) hydrogen chloride aqueous solution, and the polymer was recovered by filtration. Then, a large amount of deionized water was used for precipitation purification. Finally, the purified polymer was dried and collected under vacuum conditions.
[0079] Examples 1-5
[0080] The proportions of groups A, B, and C in Examples 1-5 are shown in Table 2, and the proportions of each component in Examples 1-5 are shown in Table 3.
[0081] Table 2
[0082] A 15 20 30 25 30 B 4 8 8 5 5 C 0.5 1 0.5 0.6 0.8
[0083] Table 3
[0084]
[0085]
[0086] The preparation steps of an organosilicon marine antifouling coating with mussel-like adhesion in Examples 1-5 are shown below. In actual application, it is prepared according to the conventional method of marine antifouling coating, and is not limited to this preparation method.
[0087] (1) Hydroxyl-terminated polysiloxane resin, dopamine-modified polysiloxane polymer, additives, and 50% of the first solvent were added sequentially to a dispersion and stirring device. The mixture was then dispersed at 100 rpm for 20 min. After that, pigments and fillers and 50% of the first solvent were added to the dispersion and stirring device, and the mixture was dispersed at the same speed for 20 min to prepare component A. The mixture was then sealed and stored.
[0088] (2) Use a dispersion and stirring device to disperse the curing agent and the second solvent at 50 rpm for 10 min to prepare component B, and then seal and store it.
[0089] (3) Use a dispersion and stirring device to disperse the catalyst and the third solvent at 50 rpm for 10 min to prepare component C, and then seal and store it.
[0090] (4) Mix components A, B and C evenly using conventional dispersion processes and equipment, apply the coating by spraying, rolling, brushing or other methods, and cure for at least 48 hours to prepare a coating with a thickness of 150 to 250 μm.
[0091] Comparative Example 1
[0092] Compared with Example 1, the dopamine-modified polysiloxane polymer of Comparative Example 1 did not have the RAFT reagent added during the preparation process, and the remaining components and weight parts were the same. Its preparation process was also the same as that of Example 1.
[0093] Comparative Example 2 (Ordinary silicone low surface energy marine antifouling coating)
[0094] Ordinary organosilicon low surface energy marine antifouling coating comprises the following raw materials in parts by weight: 90.0 parts polysiloxane resin, 30.0 parts pigments and fillers, 4.0 parts crosslinking curing agent, 1.5 parts catalyst, 0.5 parts additives, and 10.0 parts solvent.
[0095] The polysiloxane resin selected was α,ω-dihydroxypolydimethylsiloxane with a viscosity of 10000 mPa·s; the pigment selected was zinc oxide; the crosslinking curing agent selected was tetraethyl orthosilicate; the catalyst selected was dibutyltin disilicate; the additive selected was 0.5 parts of BYK161 dispersant from BYK Corporation; and the solvent selected was xylene.
[0096] (1) Add 90.0 parts of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 10000 mPa·s and 30.0 parts of micron-sized zinc oxide to a disperser and disperse at high speed at 300 rpm for 30 min. Then, add 0.5 parts of BYK161 dispersant from BYK Corporation to the disperser at 200 rpm and disperse for 30 min. Then grind the mixture in a sand mill until the fineness is less than 40 μm to make a pre-dispersed slurry, which is then bottled for later use.
[0097] (2) Mix 4.0 parts of tetraethyl orthosilicate and 10.0 parts of xylene evenly to prepare a crosslinking curing agent component and then bottle it for later use; mix 1.5 parts of dibutyltin disilicate and 20.0 parts of xylene evenly to prepare a catalyst component and then bottle it for later use;
[0098] (3) Before use, mix the pre-dispersed slurry, cross-linking curing agent and catalyst components evenly according to the ratio. After coating and curing, the resulting coating is a common organosilicon low surface energy marine antifouling coating with a thickness of 150-200μm.
[0099] <Specific Test Experiments and Conditions>
[0100] Test 1: Surface Free Energy
[0101] The contact angles of the cured coating surface with deionized water and diiodomethane were determined using an XG-CAMC3 fully automatic contact angle measuring instrument manufactured by Shanghai Xuanzhun Instrument Co., Ltd. Before measurement, the coating surface was cleaned with anhydrous ethanol and dried. The surface free energy of the coating was then calculated using the Owens two-liquid method.
[0102] Test 2: Pull-out method for adhesion testing (steel plate, epoxy intermediate paint)
[0103] The adhesion of coatings applied to the corresponding substrates or epoxy intermediate paints was measured using a BGD500 digital display semi-automatic adhesion tester manufactured by Guangzhou Biaogeda Precision Instruments Co., Ltd. The steel plates needed to be sanded with 800-grit sandpaper before use, and the epoxy intermediate paint used was epoxy micaceous iron oxide intermediate paint manufactured by Shanghai Jinshidi.
[0104] Test 3: Stain Resistance
[0105] A strain containing at least 10⁸ units of *Streptococcus salivarius* was dispersed in 20 mL of trypsin-soy broth and incubated at 38 °C with 5% CO₂ for 2 hours. The suspension was then further diluted and inoculated onto agar supplemented with 5% sheep blood, and incubated at 38 °C with 5% CO₂ for 48 hours. Units containing six colonies were then dispersed in 10 mL of trypsin-soy broth. A 20 mL layer of the above bacterial suspension was then applied to a 10 × 5 cm area and incubated at 38 °C with 5% CO₂ for 24 hours. After incubation, each sample was swirled in 45 mL of distilled water for 30 seconds, followed by rinsing with 50 mL of distilled water to remove non-adhesive material. The bacteria adhering to the surface were observed using a Carl Zeiss Simga 300 scanning electron microscope.
[0106] The specific test results of Examples 1-5 and Comparative Examples 1-2 are shown in Tables 4 and 5.
[0107] Table 4
[0108]
[0109] Table 5
[0110]
[0111] The above tests confirm that both the example and comparative coatings exhibit low surface free energy, thus demonstrating excellent antifouling performance. The advantage of this invention lies in the fact that the examples show superior adhesion to various polar substrates, far exceeding that of the comparative examples, exhibiting excellent bonding effects.
[0112] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. An organosilicon marine antifouling coating for preventing mussel adhesion, characterized in that, By weight fraction, it includes: (1) 15 to 30 parts of component A; (2) 4 to 8 parts of component B; and (3) 0.5 to 1 part of component C. in, Component A comprises, by weight: 60-100 parts of hydroxyl-terminated polysiloxane resin 20-50 parts of dopamine-modified polysiloxane polymer 1-3 parts of auxiliary agent 40-60 parts of pigments and fillers 50-80 parts of the first solvent; Component B comprises, by weight: 10-20 parts of curing agent 40-100 parts of the second solvent; Component C comprises, by weight: 5-10 parts of catalyst The third solvent is 15-30 parts; The dopamine-modified polysiloxane polymer was prepared by a combination of free radical copolymerization and ammonolysis, with the specific steps as follows: (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ type silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent are added in sequence, and then the temperature is raised to 65~75℃ and reacted for 5~8h. (2) Pour the reaction product into methanol at 5°C and filter it multiple times. Dry the filtered product under vacuum to obtain the prepolymer. (3) In an argon-protected reactor, add the prepolymer, followed by the dried dimethylformamide, dopamine salt monomer, and triethylamine, and then stir the reaction at room temperature for 20-26 hours. (4) The product after the reaction was precipitated in an excess of 0.5wt% hydrogen chloride aqueous solution, and the polymer was recovered by filtration. Then, a large amount of deionized water was used for precipitation purification. Finally, the purified polymer was dried and collected under vacuum conditions. The unsaturated pentafluorophenol ester monomer is selected from pentafluorophenyl acrylate, pentafluorophenyl methacrylate, and 4-vinylphenyl pentafluorobenzoate; the unsaturated MQ type silicone resin is selected from methyl vinyl MQ type silicone resin with an M:Q value ≥ 1.3:1, or methyl vinyl MQ type silicone resin is liquid at 25°C; the unsaturated acrylate monomer is selected from butyl methacrylate, laurate methacrylate, and butyl acrylate; the chain transfer agent is a RAFT reagent; the dopamine salt monomer is selected from 6-hydroxydopamine hydrochloride, dopamine hydrochloride, and 5-hydroxydopamine hydrochloride. The weight ratio of unsaturated pentafluorophenol monomer, unsaturated MQ type silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent is 2:(30~45):(5~10):(0.1~0.4):(0.5~1):(40~80); The weight ratio of the prepolymer, dimethylformamide, dopamine salt monomer, and triethylamine is (30~50):(50~120):(3~5):(5~10).
2. The coating as described in claim 1, characterized in that, The hydroxyl-terminated polysiloxane resin is selected from α,ω-dihydroxy polydimethylsiloxane with a viscosity of 2800-10000 mPa·s at 25°C.
3. A method for preparing a coating as described in any one of claims 1-2, characterized in that, Specifically, the steps include the following: (1) Add hydroxyl-terminated polysiloxane resin, dopamine-modified polysiloxane polymer, additives, and 50% of the first solvent in sequence to the dispersion and stirring equipment, and then disperse at 100 rpm for 20 min. Then add pigments and fillers and 50% of the first solvent to the dispersion and stirring equipment, and continue to disperse at the same speed for 20 min to prepare component A. Then seal and store. (2) Use a dispersion and stirring device to disperse the curing agent and the second solvent at 50 rpm for 10 min to prepare component B, and then seal and store it. (3) Use a dispersion and stirring device to disperse the catalyst and the third solvent at 50 rpm for 10 min to prepare component C, and then seal and store it.
4. The antifouling coating prepared by the coating as described in any one of claims 1-2, characterized in that, Mix components A, B, and C evenly, apply the mixture to a substrate, and cure for at least 48 hours to prepare a coating with a thickness of 150~250 μm.
Citation Information
Patent Citations
Surface coating polymer, and preparation method and application thereof
CN110054732A
Polymeric material and preparation method thereof
CN115651123A
Functionalized modified fouling release type marine antifouling paint
CN118813135A